Hypothesis: inflammatory acid-base disruption underpins Long Covid - van der Togt, Vicky; Rossman, Jeremy S. (Frontiers in Immunology, 2023)
The mechanism of Long Covid (Post-Acute Sequelae of COVID-19; PASC) is currently unknown, with no validated diagnostics or therapeutics. SARS-CoV-2 can cause disseminated infections that result in multi-system tissue damage, dysregulated inflammation, and cellular metabolic disruptions. The tissue damage and inflammation has been shown to impair microvascular circulation, resulting in hypoxia, which coupled with virally-induced metabolic reprogramming, increases cellular anaerobic respiration. Both acute and PASC patients show systemic dysregulation of multiple markers of the acid-base balance. Based on these data, we hypothesize that the shift to anaerobic respiration causes an acid-base disruption that can affect every organ system and underpins the symptoms of PASC. This hypothesis can be tested by longitudinally evaluating acid-base markers in PASC patients and controls over the course of a month. If our hypothesis is correct, this could have significant implications for our understanding of PASC and our ability to develop effective diagnostic and therapeutic approaches.